Development of Superficial Scald in 'Washington Spur' Apples Grown Under Anti-Hail Nets and Stored Using Conventional Cold Storage Method - Castro, Andrea Lucia; Del Brio, Josefina; Vicente, Ariel Roberto; Raffo Benegas, Maria Dolores; Calvo, Gabriela (ISHS, 2026)
Póster y resumen